Geometry and Cenozoic evolution of the Crimean fold-thrust belt from cross-section balancing and kinematic forward modeling - Nakapelyukh, M.; Belskyi, V.; Ratschbacher, L. (Геофизический журнал, 2018)
The Crimean fold-thrust belt comprises the onshore Crimean-dome fold-thrust belt and the offshore Sorokin accretionary wedge, a sub-surface imbricate stack with high oil and gas potential. We combine geomorphological and balanced cross-section analyses with published low-temperature thermo¬chronology and offshore seismic data to constrain both its present geometry and Cenozoic structural evolution. We interpret the Crimean dome as a map-scale, ramp-related antiform above the Main Crimean thrust, the basal detachment to the onshore part of the fold-thrust belt. The Main Crimean thrust separates the continental Scythian plate from the transitional to oceanic Eastern Black-Sea basin and likely reactivates an Upper Triassic–Lower Jurassic passive continental margin structure. The Crimean fold-thrust belt has accommodated ~24 km shortening since the Eocene, with ~12 km contraction each in the thick-skinned Crimean dome and the thin-skinned Sorokin accretionary wedge. The intermediate geometries in the kinematic evolution traced by the kinematic forward model are testable by future hydrocarbon exploration and thermochronologic studies.